Melatonin and alpha lipoic acid attenuate methotrexate/ cisplatin-induced kidney toxicity in albino rats - Elias Adikwu; Nelson Clement Ebinyo; Bonsome Bokolo (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Most anticancer therapies are seldom effective by single anticancer drug due to biologic heterogeneity and multiple genetic alterations stimulating the use of anticancer drug combinations. Methotrexate/cisplatin (MTX/CPT) has shown beneficial effects in the treatment of metastatic and malignant tumors, but its use may perturb kidney function. Objectives: The present study assessed the protective effects of melatonin (MT) and alpha-lipoic acid (ALA) against kidney toxicity induced by MTX/CPT in albino rats. Materials and Methods: Forty-eight adult male albino rats were randomized into groups and pretreated with MT (10 mg/kg), ALA (10 mg/kg) and MT+ALA daily for five days before treatment with 20 mg/kg of MTX and 5 mg/kg of CPT intraperitoneally on the fifth day. After overnight fast, rats were sacrificed, serum samples were centrifuged from blood samples and assessed for renal function parameters and electrolytes. Kidneys were assessed for oxidative stress (OS) markers and pathology. Results: Significant (P<0.001) increases in serum creatinine, urea, and uric acid levels with significant (P<0.001) decreases in total protein, albumin, potassium, sodium, chloride, and bicarbonate levels were obtained in MTX/CPT-intoxicated rats when compared to control. Furthermore, kidney malondialdehyde levels were significantly (P<0.001) increased whereas catalase, superoxide dismutase, glutathione and glutathione peroxidase levels were significantly (P<0.001) decreased in MTX/CPT-intoxicated rats when compared to control. Pathologic changes marked by atrophic glomeruli were detected in the kidneys of MTX/CPT-treated rats. However, nephrotoxicity observed in MTX/CPT-treated rats was significantly reversed in MT (P<0.01), ALA (P<0.05) and MT+ALA (P<0.001) pretreated rats when compared to MTX/CPT -treated rats. Conclusion: MT and ALA supplementations attenuate nephrotoxicity caused by MTX/CPT.